PENGARUH KUALITAS PELAYANAN TERHADAP NASABAH PADA BANK SUMUT SYARIAH CAPEM MARELAN RAYA - Devita; Ahmad Riadi Daulay (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of service quality on customer satisfaction at Bank Sumut Syariah Capem Marelan Raya. The research method used is qualitative with a field study approach, through observation and in-depth interviews with the Deputy Leader of the Bank. The results showed that service quality has a significant influence on customer satisfaction, where reliability, responsiveness, and assurance are the most dominant dimensions. This research implies the importance of continuous improvement of service quality, focusing on these key dimensions, to increase customer loyalty and bank performance